ANTI-COMMUNISM AND SOCIAL CONTROL IN CHILE, THE EXPERIENCE OF THE COAL WORKERS IN LOTA AND CORONEL, BY THE MIDDLE OF THE XX TH CENTURY - Venegas Valdebenito, Hernán (Revista de Historia Social y de las Mentalidades, 2013)
In the early 1940’s coal region in Chile was strongly influenced by the Communist Party, a situation contradicted, according to employers and national authorities, the strategic nature of this industry in the whole national economy. The paper examines some political and business visions about the problem and, moreover, describes the mechanisms that tried to stop the mobilization of workers and the communist advance, severely straining social relations in the area. Since then the workers’ demands inevitably wore out, a phenomenon reinforced further by the loss of relative importance of coal in the Chilean economy.